2017
DOI: 10.1016/j.eurpsy.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to tobacco smoke in utero or during early childhood and risk of hypomania: Prospective birth cohort study

Abstract: Objectives Using data from a prospective birth cohort, we aimed to test for an association between exposure to tobacco smoke in utero or during early development and the experience of hypomania assessed in young adulthood.Methods We used data on 2,957 participants from a large birth cohort (Avon Longitudinal Study of Parents and Children, ALSPAC). The primary outcome of interest was hypomania, and the secondary outcome was 'hypomania plus previous psychotic experiences (PE)'. Maternally-reported smoking during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Firstly, although systematic reviews are accepted as the highest in the evidence hierarchy [76,77], the focus on systematic reviews alone meant some health conditions were not covered. Some original studies have indicated the impact of SDP on other infant-related conditions, such as diabetes [78], hypomania [79], otitis [80] and pervasive development disorder [81], which were not assessed in a systematic review, and as a result were not included in this study. Furthermore, SDP has been shown to be related to the smoking uptake of the offspring [82,83].…”
Section: Strengths and Limitations Of The Umbrella Reviewmentioning
confidence: 99%
“…Firstly, although systematic reviews are accepted as the highest in the evidence hierarchy [76,77], the focus on systematic reviews alone meant some health conditions were not covered. Some original studies have indicated the impact of SDP on other infant-related conditions, such as diabetes [78], hypomania [79], otitis [80] and pervasive development disorder [81], which were not assessed in a systematic review, and as a result were not included in this study. Furthermore, SDP has been shown to be related to the smoking uptake of the offspring [82,83].…”
Section: Strengths and Limitations Of The Umbrella Reviewmentioning
confidence: 99%
“…However, it is still unclear whether these findings are false positives resulting from a lack of power in relatively small samples. Maternal smoking during pregnancy is associated with psychotic experiences in offspring 19 . However within-family studies suggest that once familial factors are taken into account, maternal smoking during pregnancy has no effect on the risk of psychotic experiences 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In particular, recent studies have provided novel evidence of associations between SDP and offspring bipolar disorder, 4 schizophrenia, 5 and related outcomes. 6 These associations raise the possibility that SDP exposure has c ausal teratogenic eff ects on the risk of severe mental illness (SMI). 7 Because nicotine and carbon monoxide cross the placenta and may directly and indirectly (eg, via hypoxia) affect fetal neurodevelopment, 8 this hypothesis is biologically plausible.…”
mentioning
confidence: 99%